Identifikasi Daerah Patahan dengan Metode Geolistrik Konfigurasi Dipole-Dipole di Desa Renokenongo Porong Sidoarjo - Sri Cahyo Wahyono; Totok Wianto; Simon Sadok Siregar; Widya Utama; Suminar pratapa (Lambung Mangkurat University Press, 2008)
Fault is already occurred in Renokenongo, Porong - Sidoarjo. These fault’s have destroyed some building and public facilities. Existence of these fault’s have been detected by using 2D resistivity method. In this research, measurement of 2D resistivity is conducted by using Dipole-Dipole configuration. Configuration has been done in two lines. The first line is length of measurement 200 meters and direction E 98° S and second line the path lenght of 120 meters and direction N 50 E. From the resistivity section, position of fault is founded. For first line, position of fault stays at point 25; 43; 57; 97,5; 110 and 136 m. While for second line position of fault stays at point 33; 50 and 100 m.